An integrated approach of a field‐circuit coupling model and multi‐physics finite‐element simulation for analysing transient electromagnetic vibration of pump motors. Issue 9 (26th May 2022) - Zhao, Jin; Zhang, Qing; Wei, Xiaohan
Abstract: We propose a method to investigate the generation mechanism of the transient vibration of a pump motor induced by electromagnetic (electromagnetic (EM)) forces. Compared with the steady vibration of a pump motor, the transient vibration characterised by a wider excitation frequency spectrum and larger instantaneous amplitude makes the vulnerable structure more easily exposed to potential damage. However, transient vibration of pump motor has not been analysed and verified before. Based on the fact that EM vibration dominates the vibration of pump motors, in this study, an approach which integrates the field‐circuit coupling method and multi‐physics finite‐element (finite‐element (FE)) simulation is proposed to estimate the structural response of pump motors under transient operating conditions. To determine the factors that determine the EM forces, an analytical model describing the transient interaction between the EM and the fluid torque is first created. It was revealed that the input voltage and slip rate are two key factors that affect the transient EM forces. Then, to quantitatively describe the transient EM forces governed by a specific control scheme during the start‐up process, a field–circuit coupling model embedding in the control scheme, electrical circuit model, motor FE model, and rotor dynamic model is established. This model allows the circuit equations, rotor dynamics equations, and magnetic field equations to be solved simultaneously. The transient EM forces obtained by the field–circuit coupling model provide excitation for the structural response calculation. Subsequently, a multi‐physics FE simulation, which takes a weak coupling strategy between the EM and structural dynamics fields, is utilised to link the different physical domains. Thus, the EM forces are transferred to a structural domain to compute the structural response by adopting a direct integration method. The integration approach developed in this study was verified on the pump motors in the main cooling units of ultra‐high voltage (UHV) converter stations. The trends of dominant components of simulated signals agree with the measured signals from the pump motors. This indicates that the proposed method can be widely applied for the transient vibration analysis and mitigation for pump motors.